The Jews should keep quiet : Franklin D. Roosevelt, Rabbi Stephen S. Wise, and the Holocaust - Medoff, Rafael, 1959- (University of Nebraska Press, 2019)
"Based on recently discovered documents, The Jews Should Keep Quiet reassesses the hows and whys behind the Franklin D. Roosevelt administration's fateful policies during the Holocaust. Rafael Medoff delves into difficult truths: With FDR's consent, the administration deliberately suppressed European immigration far below the limits set by U.S. law. His administration also refused to admit Jewish refugees to the U.S. Virgin Islands, dismissed proposals to use empty Liberty ships returning from Europe to carry refugees, and rejected pleas to drop bombs on the railways leading to Auschwitz, even while American planes were bombing targets only a few miles away--actions that would not have conflicted with the larger goal of winning the war. What motivated FDR? Medoff explores the sensitive question of the president's private sentiments toward Jews. Unmasking strong parallels between Roosevelt's statements regarding Jews and Asians, he connects the administration's policies of excluding Jewish refugees and interning Japanese Americans. The Jews Should Keep Quiet further reveals how FDR's personal relationship with Rabbi Stephen S. Wise, American Jewry's foremost leader in the 1930s and 1940s, swayed the U.S. response to the Holocaust. Documenting how Roosevelt and others pressured Wise to stifle American Jewish criticism of FDR's policies, Medoff chronicles how and why the American Jewish community largely fell in line with Wise. Ultimately Medoff weighs the administration's realistic options for rescue action, which, if taken, would have saved many lives."--